The Development of Social Communication Skills and Socially Acceptable Behavior in Children with ASD within the Organized Excursion Activities - S.P. Popova (Moscow State University of Psychology and Education, 2021)
The data on the implementation of the program of additional education "Environmental Holidays in the Museum'' presented. Program aimed at the development of social and communication skills of students with autism spectrum disorders (ASD). The events held in the 2019-2020 academic year in cooperation with the professionals of the Yalu- torovsk Museum Complex of the Tyumen Region. For the implementation of the program, an integrated group of younger schoolchildren was organized, consisting of 5 children with ASD and 9 children with visual impairments. Age of the group participants varied from 8 to 11 years. Following methods were used during presented work: observation, social stories, polls. Most of the classes conducted in a playful and interactive form based on the museum, each was built taking into account the age and psychological characteristics of the students. Nine field excursions conducted. As a result, all children with ASD showed positive dynamics in the development of socially acceptable behavior and a positive attitude to the new format of educational work, and there were attempts to interact with peers and outside adults. A survey of parents confirmed the positive dynamics in the develpment of certain communication and social skills of their children.